Latent tuberculosis among injection drug users in a methadone maintenance treatment program, Taipei, Taiwan: TSPOT.TB versus tuberculin skin test. (July 2013) - Yen, Yung-Feng; Hu, Bor-Shen; Lin, Yu-Shiuan; Li, Lan-Huei; Su, Lien-Wen; Chuang, Peing; Lin, Nai-Ching; Jiang, Xiao-Ru; Shie, Ying-Huei; Chang, Hsiao-Hui; Ou, Wei-Xian; Zhan, Hong-Jun; et al.
Abstract Background: Taiwan has a growing HIV/AIDS epidemic that has recently shifted to an increase among injection drug users (IDUs). IDUs co-infected with HIV and tuberculosis (TB) have a high risk of progression from latent tuberculosis infection (LTBI) to active TB. Methods: This study aimed to determine the prevalence and correlates of LTBI among IDUs by TSPOT.TB and tuberculin skin test (TST), in a large methadone program in Taipei, Taiwan. Consenting participants were interviewed by a trained worker regarding sociodemographics, substance use history, and health factors. Results: Multivariate analysis was used to determine risks associated with each test outcome. Of 287 participants, 165 (58.7%) tested TSPOT.TB-positive and 244 (85.0%) tested TST-positive. The mean age was 44 y, and 7.3% were HIV-infected. Kappa statistics indicated slight concordance between TSPOT.TB and TST. In multivariate analysis, after controlling for potential confounders, TSPOT.TB positivity was significantly associated with age ≥ 50 y (reference, 20–34 y). A history of ever having had contact with a TB-infected person was associated with TST positivity, whereas HIV infection was inversely associated with TSPOT.TB positivity and TST positivity. Conclusions: This study shows a high prevalence of LTBI in individuals at risk for HIV infection in Taipei, Taiwan. Future TB prevention programs should particularly focus on IDUs.